2003
DOI: 10.1038/sj.jhh.1001608
|View full text |Cite
|
Sign up to set email alerts
|

Higher blood pressure in middle-aged American adults with less education—role of multiple dietary factors: The INTERMAP Study

Abstract: Extensive evidence exists that an inverse relation between education and blood pressure prevails in many adult populations, but little research has been carried out on reasons for this finding. A prior goal of the INTERMAP Study was to investigate this phenomenon further, and to assess the role of dietary factors in accounting for it. Of the 4680 men and women aged 40-59 years, from 17 diverse population samples in Japan, People's Republic of China, UK, and USA, a strong significant inverse education-BP relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 20 publications
(28 reference statements)
3
49
1
4
Order By: Relevance
“…Therefore, the level of schooling is an essential element to be considered in the approach of the population regarding the practices of health promotion, protection and recovery 21 . Some population-based crosssectional studies also found an inverse correlation between schooling and AH prevalence 8,18,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the level of schooling is an essential element to be considered in the approach of the population regarding the practices of health promotion, protection and recovery 21 . Some population-based crosssectional studies also found an inverse correlation between schooling and AH prevalence 8,18,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Эти выводы поддерживали стратегическую концепцию в отношении усилий здравоохранения для улучшения питания низших социально-эконо-мических слоев населения, а также помогали внести важный вклад в профилактику, контроль АГ и дру-гих основных ФР ССЗ [2,16].…”
Section: обзорыunclassified
“…Питание, в первую очередь, рассматривается с точки зрения предотвращения ожирения, артери-альной гипертензии (АГ), нарушений углеводного и липидного обменов. Нарушение пищевого пове-дения и дисбаланс между поступлением и тратой калорий являются основной причиной ожирения; чрезмерное потребление натрия и высококалорий-ной пищи, алкоголя инициирует повышение арте-риального давления (АД) [1,2]. Общепризнано, что жиры животного происхождения в рационе ассоци-ированы с развитием атеросклероза [3], их повы-шенное содержание в продуктах питания увеличи-вает вероятность инфаркта миокарда, ишемиче-ского инсульта за счет повышения концентрации липопротеидов низкой плотности [4,5].…”
unclassified
“…The ability to monitor exposure to xenobiotics, which may not be toxic in their own right, but which may carry a risk to certain individuals in populations after long term exposure, is an important in the broad context of epidemiological risk assessment and allows connection between 'real world' analytical data and epidemiological factors. Recently we have applied NMR spectral tools to the investigation of biochemical features of the urine samples collected as part of the INTERSALT and INTERMAP Studies [2,3], which investigate the role of nutrition in adverse population blood pressure levels [4][5][6][7][8][9]. These samples were obtained from many populations and carry unique biochemical information about those groups and individuals [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%